(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the transformative role of Virtual Reality (VR) in developing English speaking skills among second-language learners. While traditional classroom settings often struggle to provide authentic, high-stakes conversational practice, VR technology offers a unique solution by creating immersive, three dimensional worlds. This study examines how these simulated environments help reduce learner anxiety, promote "spatial presence," and provide realistic contexts for communication. By analyzing the psychological and pedagogical benefits of VR, the article argues that immersive technology is moving from a futuristic concept to an essential tool for achieving oral fluency in the digital age.